2003
DOI: 10.1179/030192303225009579
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of narrow face water slot design for Siderar slab casting mould

Abstract: investigations carried out included the study of a used plate and an analysis of the continuous casting mould narrow A study of a mould narrow plate was carried out at plate by means of a nite element model (Fig. 1). The purpose Instituto Argentino de Siderurgia (IAS), to assess of the work was to study whether too high a temperature the plate condition after its life, in this case 2227 in the narrow plate could be generating a distortion of the heats. A finite element model of steady heat mould corner below t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Chow et al 1) applied a mathematical billet thermal model to the heat transfer results from a high casting speed instrumented mold trial to provide a new mold taper for minimizing mold-strand interaction. Thomas and Liu et al 2,3) investigated the relation between copper plate geometry of mold and temperature distribution on the basis of a finite-element heat-transfer model and evaluated the mold design. Lu et al 4) indicated that the main factors on mold temperature are thickness of copper plate and plated nickel layer through a heat transfer model for slab casting.…”
Section: Introductionmentioning
confidence: 99%
“…Chow et al 1) applied a mathematical billet thermal model to the heat transfer results from a high casting speed instrumented mold trial to provide a new mold taper for minimizing mold-strand interaction. Thomas and Liu et al 2,3) investigated the relation between copper plate geometry of mold and temperature distribution on the basis of a finite-element heat-transfer model and evaluated the mold design. Lu et al 4) indicated that the main factors on mold temperature are thickness of copper plate and plated nickel layer through a heat transfer model for slab casting.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, many efforts have been conducted by developing mathematical models to calculate the shrinkage of solidifying shell in mold with/without the consideration of the mold wall distortion in past decades, and several types of square billet and round billet mold tapers have been proposed and applied in practical continuous casting. 1,6,7,[12][13][14][15][16][17][18]22) However, less attention [2][3][4][5][8][9][10][11][19][20][21] has been paid to the optimization of slab continuous casting mold taper despite numerous studies [23][24][25][26][27][28][29][30] of shell thermo-mechanical behavior in slab mold have been conducted. Currently, most of the practical slab continuous casting molds adopt the conventional mold taper of linear constant narrow face with ignoring the wide face structures since slab continuous casting is characterized the large ratio of width/thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, most of the practical slab continuous casting molds adopt the conventional mold taper of linear constant narrow face with ignoring the wide face structures since slab continuous casting is characterized the large ratio of width/thickness. Thomas and his coworkers 2,3,5,[8][9][10] predicted the curvilinear slab mold tapers of narrow face at different casting conditions according to the shrinkage profiles of shell along mold height. Similarly, Matoba et al 11) also proposed a multi-tapered narrow face mold that the upper part was set as parabola while the linear taper was given at lower part according to the deformation behavior of solidifying shell in slab continuous casting mold.…”
Section: Introductionmentioning
confidence: 99%
“…The service life of the large hole mould is ,200 heats less than that of small hole mould before each remachining, and the service time of both moulds decreases after each grinding. 4. After 500 and 1000 heats of casting respectively, the crack rates of beam blank cast by the small hole mould are 4?10 and 6?85% lower than those of the large hole mould.…”
Section: Discussionmentioning
confidence: 96%